Reading and Writing Competences in Music. An Approach to their Incorporation into the School Curriculum - Cárdenas Soler, Ruth Nayibe; Martínez Álvarez, Juan Diego; Cremades Andreu, Roberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Music is a language that is able to reach all of its listeners. It emerges from the use of musical notation for its composition, and passes through a decoding process, to finally obtain an interpretation of the musical message. For this reason, it can be said that music is a non-native language, one that can be understood by anyone without needing to know its code. In this article an analysis of the concept of reading and writing competences in music is proposed, locating it specifically in the field of reading and writing in language, understanding that music uses a system of signs and codes which may be applied to the aforementioned communicative skills. As a result of this analysis, an approach to the incorporation of reading and writing competences in music is proposed for the school curriculum. This project aims at contributing to the discussion about the way musical education should be implemented in schools.